A study on rehabilitated drug addicts and society acceptance towards a rehabilitated life - Mohamad Noor, Norazleen; Kumar, Ashwin (Human Resource Management Academic Research Society, 2017)
The January-December 2013 AADK (Agensi Anti Dadah Kebangsaan) report, one of the contributing factors towards relapse cases in drug addiction is lack of social support from the society when they re-enter the community. To date, studies investigating this aspect are still limited. The current study investigates the aspects of rehabilitated drug addicts and society support or backing perceived by former drug addicts to a rehabilitated life. In-depth interview will be conducted to examine the respondents. The interview will took almost 35 minutes each and open-ended questions will be asked for further investigates the reasons of the relapse. Interviews will also be conducted with society representatives, legal and lawful professions to further investigate issues on studies from a neutral point of view. Overall the result hopes to shows the important agents that can help drug addicts to return to a normal life. The important mechanisms of society support are emotional, practical assistance, socializing, financial assistance, advice or motivation and a caring guidance. Additionally, the post-rehabilitation program should emphasize in providing in a concrete support groups for the rehabilitated addicts.